Effect of different carriers on In Vitro and In Vivo drug release behavior of Aceclofenac Proniosomes - Sammour, Rana M. F.; Chatterjee, Bappaditya; Taher, Muhammad; Saleh, Mohammed S.M.; Shahiwala, Aliasgar (NLM (Medline), 2021)
Improved bioavailability of Aceclofenac (ACE) may be achieved through proniosomes, which are considered as one of the most effective drug delivery systems and are expected to represent a valuable approach for the development of better oral dosage form as compared to the existing product. However, the carrier in this system plays a vital role in controlling the drug release and modulating drug dissolution.Accordingly, a comparative study on different carries can give a clear idea about the selection of carries to prepare ACE pronisomes.